Significance of Cuscutain, a cysteine protease from Cuscuta reflexa, in host-parasite interactions - Bleischwitz, Marc; Albert, Markus; Fuchsbauer, Hans-Lothar; Kaldenhoff, Ralf (BMC Plant Biology, 2010)
Background: Plant infestation with parasitic weeds like Cuscuta reflexa induces morphological as well as biochemical changes in the host and the parasite. These modifications could be caused by a change in protein or gene activity. Using a comparative macroarray approach Cuscuta genes specifically upregulated at the host attachment site were identified.Results: One of the infestation specific Cuscuta genes encodes a cysteine protease. The protein and its intrinsic inhibitory peptide were heterologously expressed, purified and biochemically characterized. The haustoria specific enzyme was named cuscutain in accordance with similar proteins from other plants, e.g. papaya. The role of cuscutain and its inhibitor during the host parasite interaction was studied by external application of an inhibitor suspension, which induced a significant reduction of successful infection events.Conclusions: The study provides new information about molecular events during the parasitic plant - host interaction. Inhibition of cuscutain cysteine proteinase could provide means for antagonizing parasitic plants. © 2010 Bleischwitz et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2020-03-09